Marketing Strategy for Cricket Livestock Business in Maccini Baji Village, Bajeng District, Gowa Regency - Iskharul Haq; Haedar Akib; Maya Kasmita; Syarifuddin Syarifuddin (Pinisi Business Administration Review, 2026)
This research examines the Marketing Strategy for Cricket Livestock Business in Maccini Baji Village, Bajeng District, Gowa Regency. This type of qualitative research with descriptive research type. The data sources used in this research are primary data and secondary data. Data collection procedures used in this study are observation techniques, interview techniques, documentation techniques. Data validity tests in qualitative research include tests of credibility (internal validity), transferability (external validity), dependability (reliability) and confirmability (objectivity). The results of the study show that the availability of large tracts of land provides great potential for developing cricket farming businesses as pet feed . The support of high market demand for crickets is an important factor in adding new, wider cages. In addition, the local government's desire to develop cricket farms is realized through the provision of counseling and micro credit loan capital assistance to MSMEs. Good road access in cricket farming areas also facilitates distribution to markets and reduces operational costs. Capital assistance to small-scale farmers, increasing human resources through counseling, maintaining egg quality, and increasing business management capabilities are important factors in the development of cricket farms. Collaboration with government programs that focus on biosecurity is also needed to increase the success of the cricket farming business as pet feed.